THE USE OF WORDWALL ONLINE GAME IN TEACHING VOCABULARY TO STUDENTS AT SMKN 2 PALOPO - Sapna; Madehang; Usman, Nurhayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sapna, 2026. This study investigates the effectiveness of the Wordwall online game application in improving English vocabulary mastery among 11th-grade students in class TKJ A at SMKN 2 Palopo. The problem identified is that students generally struggle with vocabulary mastery, which affects their overall English language skills including speaking, writing, and reading. This research employs a pre-experimental design with a one-group pre-test and post-test approach. The population consisted of 19 students in class XI TKJ A at SMKN 2 Palopo, with all students used as the research sample through total sampling technique. The research instrument used was a multiple-choice vocabulary test, and data were analyzed using a paired sample t-test. The results showed a significant increase in mean scores from 50.74 in the pre-test to 74.74 in the post-test. The t-count value (t₀ = 5.871) exceeded the t-table value (tₜ = 2.101) at a significance level of 0.05 with 18 degrees of freedom. Consequently, the alternative hypothesis (H₁) was accepted and the null hypothesis (H₀) was rejected. These findings confirm that the use of Wordwall online games is effective in improving ESP (English for Specific Purposes) vocabulary mastery of students at SMKN 2 Palopo.